Perceptions of risk to compound coastal water events: A case study in eastern North Carolina, USA - Scott Curtis; Anuradha Mukherji; Jamie Kruse; Jennifer Helgeson; Ausmita Ghosh; Nelson Adeniji (Progress in Disaster Science, 2022)
It is recognized that compound coastal water events (CCWE) - the combination of rain, river, and ocean flooding - often have increased disastrous consequences as compared to single-form floods due to their physical complexity. However, another potential reason is the lack of adequate understanding and effective response by hazard professionals. In rural eastern North Carolina (ENC), an under-resourced and CCWE-vulnerable region of the US, we survey and interview a focus group of primarily emergency managers and planners about their understanding of CCWE risk and the perceived obstacles in communicating this risk to their constituents. Likely due to recent hurricanes, hazard professionals in ENC are anecdotally aware of the sources and timing of floods in their communities, and the eleven counties represented in the study are quick to share data and experiences with each other. However, they see pluvial flooding outside of hurricanes as a growing problem and disclosed that risk communication to the public is a challenge because of a lack of tools and data to adequately describe CCWE. Finally, our case study participants felt they had a better understanding of CCWE than their state and federal counterparts and wanted to be more involved in response and recovery decision-making.